Integrated biorefineries for repurposing of food wastes into value-added products - Narisetty, Vivek; Adlakha, Nidhi; Singh, Navodit Kumar; Dalei, Sudipt Kumar; Prabhu, Ashish A.; Nagarajan, Sanjay; Kumar, A. Naresh; Nagoth, Joseph Amruthraj; Kumar, Gopalakrishnan; Singh, Vijai; Kumar, Vinod (Elsevier, 2022)
Food waste (FW) generated through various scenarios from farm to fork causes serious environmental problems when either incinerated or disposed inappropriately. The presence of significant amounts of carbohydrates, proteins, and lipids enable FW to serve as sustainable and renewable feedstock for the biorefineries. Implementation of multiple substrates and product biorefinery as a platform could pursue an immense potential of reducing costs for bio-based process and improving its commercial viability. The review focuses on conversion of surplus FW into range of value-added products including biosurfactants, biopolymers, diols, and bioenergy. The review includes in-depth description of various types of FW, their chemical and nutrient compositions, current valorization techniques and regulations. Further, it describes limitations of FW as feedstock for biorefineries. In the end, review discuss future scope to provide a clear path for sustainable and net-zero carbon biorefineries.
Keywords: Food waste; Biosurfactants; Biopolymers; Diols; Bio-methanation